Determination of sensitivity of streptococcus spp antimicrobials in positive breastfeeding cows to california mastitis test in the cordillera department-Paraguay (Veterinary Science, 2020)
The present research work was carried out in 6 milking parlors of the Cordillera Department. The objective of the research was to determine the sensitivity to antimicrobials of Streptococcus spp. from milk samples from lactating cows positive to California Mastitis Test in the dairy farms mentioned in 2018. For this purpose, 200 bovine were counted, of milk aptitude, in lactation, without distinction of race or age, of which 141 (70,5%) were positive to the California Mastitis Test (CMT). The positive samples were identified, refrigerated and sent to the laboratory of the Department of Microbiology and Immunology of the Faculty of Veterinary Sciences of the National University of Asunción, where the corresponding microbiological analyzes were performed. The laboratory results obtained indicated that of the 141 samples analyzed in 89 (63,12%), bacterial microorganisms were isolated; 26 (29,21%) corresponding to Streptococcus spp.; of which 2 (7.69%) were sensitive to oxaciline; 19 (73,08%) to cefotaxime; 26 (100%) to penicillin; 22 (84,61%) to erythomycin; 25 (96,15%) to clindamycin; 24 (92,30%) to chloramphenicol; 15 (57,69%) to tetracycline;22 (84,61%) at teicoplanine and 25 (96,15%) were sensitive to rifampicin.
Keywords: Microbial sensitivity; Streptococcus spp; antimicrobials; lactating cows; California Mastitis Test.